Balancing intellectual monopoly privileges and the need for essential medicines - Faunce Thomas; Sorenson Corinna; Martin Greg (BMC, 2007)
Abstract This issue of Globalization and Health presents a paper by Kerry and Lee that considers the TRIPS agreement and the recent policy debate regarding the protection of public health interest, particularly as they pertain to the Doha Declaration. In this editorial, we consider the debate, the conclusions thereof, and identify five questions that should be considered by key stakeholders in ongoing discussions.